Management science in hospitality and tourism : theory, practice, and applications - Uysal, Muzaffer, (Advances in hospitality and tourism book series., 2016)
"Management Science in Hospitality and Tourism is a timely and unique book focusing on management science applications in tourism and hospitality settings. The academic scope of management science in today's world is rather interdisciplinary and not always necessarily quantitative. The books includes such topics as: quantitative approach to tourism systems; monitoring and forecasting tourist activities; measuring forecasting accuracy in hospitality; big data analytics and information system; best-worst scaling method; partial least squares structural equation modeling (PLS-SEM); demand analysis in tourism; frontier approaches to performance measurement in hospitality and tourism; evidence-based analytics for productivity measurement; capacity management using time series; gravity model; shift-share analysis; destination attractiveness and performance measures; overbooking research in hospitality; tourist satisfaction, an index approach; general performance measures in hospitality."--